Polymetallic Complexes-Part XXIX: Complexes of Cobalt(II), Nickel(II), Copper(II), Zinc(II), Cadmium(II)and Mercury(II) with Chelating ON-NO Donor Azo Dye Ligands - B. Mahapatra, Bipin; Choudhury, S.C. (Asian Journal of Chemistry, 2010)
The present work describes the synthesis of two bis-bidentate azodyes, 4-(2´-hydroxyphenylazo)-8-hydroxyquinoline and 4-(2´-carboxyphenylazo)-8-hydroxyquinoline containing ON-NO donor atoms and their polymeric complexes with some divalent metal ions.